2013
DOI: 10.2190/de.43.1.a
|View full text |Cite
|
Sign up to set email alerts
|

Drug Taking Beliefs of Australian Adolescents: A Pilot Study

Abstract: In this study adolescents offered their insights and perspectives of factors associated with adolescent illicit drug taking intentions. The factors explored were identified using a cross-disciplinary approach involving the Theory of Planned Behavior (TPB) and criminological theories, and these formed the framework for data analysis. Interviews with 24 students aged 15-17 found that adolescents' beliefs to drug taking attitudes, subjective norms, perceived behavioral control, moral norms, negative affect, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Children who grow up with parents or siblings who use drugs may model behaviors and attitudes regarding substance use; through social learning processes of parental acceptance, the likelihood of substance use initiation and continuation is increased [ 45 ]. In contrast, and similar to other studies [ 19 , 30 , 37 , 42 , 43 ], we found that family beliefs against drug use are effective in preventing substance use in adolescents. Such results support the strong association between parental bonding and substance use in Moroccan adolescents from quantitative findings (unpublished data).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Children who grow up with parents or siblings who use drugs may model behaviors and attitudes regarding substance use; through social learning processes of parental acceptance, the likelihood of substance use initiation and continuation is increased [ 45 ]. In contrast, and similar to other studies [ 19 , 30 , 37 , 42 , 43 ], we found that family beliefs against drug use are effective in preventing substance use in adolescents. Such results support the strong association between parental bonding and substance use in Moroccan adolescents from quantitative findings (unpublished data).…”
Section: Discussionsupporting
confidence: 91%
“…At the individual level, the theme of perceived benefits of substance use (reflecting beliefs on the beneficial effects of substances, including cannabis, cigarettes, and edible cannabis products) was consistent with previous qualitative investigations [ 14 , 30 ]. This theme comprised two sub-themes: personal positive appeals and escape negative states.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations